1987
DOI: 10.1521/jscp.1987.5.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Personality Variables in Film-Induced Sadness and Crying

Abstract: Social and personality correlates of crying relevant to clinical application were examined in the laboratory. The effects of gender and of gender-pairing on emo tional expression of film-induced sadness were evaluated. College students served in pairs as experimental subjects. Results indicated that men retrospectively report ed less crying than women, and that both male and female subjects reported more appropriate sex-stereotypic behavior (i.e., males cried less, females cried more) when in opposite-sex pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 11 publications
2
33
1
3
Order By: Relevance
“…For men, previous studies (Choti et al, 1987;Williams, 1982) have shown associations of crying with identi®cation with feminine sex-role stereotypes, rejection of masculine sex-role stereotypes, levels of emotional empathy, and neuroticism. For women, only signi®cant positive correlations between weeping reactivity, on the one hand, and femininity and empathy, on the other hand, were found.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For men, previous studies (Choti et al, 1987;Williams, 1982) have shown associations of crying with identi®cation with feminine sex-role stereotypes, rejection of masculine sex-role stereotypes, levels of emotional empathy, and neuroticism. For women, only signi®cant positive correlations between weeping reactivity, on the one hand, and femininity and empathy, on the other hand, were found.…”
Section: Introductionmentioning
confidence: 92%
“…It has been found consistently that women cry more often and intensely than men (Choti, Marston, Holston and Hart, 1987;Frey, 1985;Frey, Hoffman-Ahern, Johnson, Lykken and Tuason, 1983;Kraemer and Hastrup, 1986;Vingerhoets and Becht, 1997;Williams and Morris, 1996; for reviews, see Vingerhoets, 1999, 2001;Vingerhoets and Scheirs, 2000). However, it remains to be established to what extent these gender differences may be attributed to differences in personality and a reluctance to express emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies in which subjects were asked to remember a recent crying episode generally suggest that crying improves mood (e.g., Bindra, 1972;Frey, Hoffman-Ahern, Johnson, Lykken, & Tuason, 1983;Kraemer & Hastrup, 1986). In contrast, laboratory studies in which participants are exposed to sad films consistently show that those who have cried feel worse and have more negative moods than those who have not shed any tears (e.g., Choti, Marston, Holston, & Hart, 1987;Gross, Fredrickson, & Levenson, 1994;Martin & Labott, 1991). The reasons for this discrepancy are unclear.…”
Section: Crying and Mood Changementioning
confidence: 99%
“…Reinforcing the idea that mood disorders may alter typical sex differences in crying, however, men (but not women) reported that the onset of depression led to increases in their crying frequency and cry proneness. Finally, there were also associations between symptom severity and crying in men, but not in women, a pattern previously found only in nonclinical samples [Choti et al, 1987;Hammen and Padesky, 1977]. We submit this study as a modest step designed to move the field toward a more differentiated picture of crying in the mood disorders Nevertheless, four limitations of the current study should be noted.…”
Section: Discussionmentioning
confidence: 59%